Pengembangan Aplikasi Arunika Education Berbasis Virtual Reality dalam Pembelajaran Teks Anekdot - Sartika, Eka; Ali, Ayu Hidayanti; Mirnawati, Mira; Hasriani, Hasriani (Ideas Publishing, 2024)
Technology is capable of providing ease in all aspects; however, in reality, in the school environment, technology has not been fully utilized. Based on this premise, this research will utilize the Arunika Eaducation application, which is based on virtual reality, in teaching anecdotal texts. The method used in this research is the R&D method. The results of this research indicate that the Arunika Eaducation application based on virtual reality is suitable for use by teachers in the classroom to improve student learning outcomes.